Relationship between Family Support and Quality of Life in Breast Cancer Patients: A Cross Sectional Study - Wulandari, Yuanita; Ulfah, Qamariyah; Mukarromah, Nur; Supatmi, Supatmi (Indonesian Academia Health Sciences Journal, 2022)
Breast cancer is still a major problem in the world of health. This is evidenced by the many cases of functional physical complications that occur. Efforts to provide support for cancer patients are very important to do in order to improve their quality of life. High family support will make the quality of life better so that the health status will be better. Individuals with high quality of life will have a strong desire to recover so that they can improve their health. Objective: This study aims to determine the relationship between family support and quality of life in breast cancer patients at the Kalijudan, Pacar Keling, and Mulyorejo health centers. Methods: The research design is quantitative with a cross-sectional approach. The research sample was 44 respondents. The questionnaire used the Family Support Scale (FSS) and The Quality of life a Breast Cancer Patient (QOL-BC). Data Analysis: Data were analyzed using Spearman rank with a significant level of 0.05. Results: The results showed that breast cancer patients who had family support in the good category were 39 respondents (88.6%), the moderate category was 5 respondents (11.4%), while the quality of life in breast cancer patients was in the good category as many as 26 respondents (59 .1%), moderate 17 respondents (38.6%), and poor 1 respondent (2.3%). The results of the Spearman Rank test show that there is a relationship between family support and quality of life with a p value of 0.029 < (α) 0.05. Discussion: Good family support affects the quality of life of breast cancer patients. Lack of family support given to breast cancer patients will result in poor quality of life of patients and vice versa good family support will make quality of life better.